Expression of a functional anti-cucumber mosaic virus single-chain variable fragment antibody in tobacco plants (nacotiana tabacum) - Chua, K.H.; Khalid, N.; Othman, R.Y. (2006)
As an alternative method to produce low cost reagents for immunodiagnosis and protect the plants from viral disease, a gene encoding a single chain variable fragment(scFv) recombinant antibody targeted to the coat protein of cucumber mosaic virus (CMV) was expressed in Nacotiana tabacum. The source of the scFv recombinant antibody gene was from spleen tissue of an immunized mouse. The gene was initially cloned into the pCANTAB5E phagemid and expressed in E. coli. In the following study, the antibody gene was subcloned into the plant expression vector, pCAMBIA-1301 and introduced into tobacco leaf tissue via Agrobacterium tumefacients mediated transformation. After transformation, 56 out of 58 plants were shown to carry the desired anti-CMV scFv gene by PCR analysis. Overall, only 12.5 of the 56 putative transgenic plants were found to express the antibody to a detectable level.